Classification of N, P, and K concentrations in durian (Durio zibethinus murray cv. mon thong) leaves using near-infrared spectroscopy - Phanomsophon, Thitima; Jaisue, Natthapon; Tawinteung, Nukoon; Khurnpoon, Lampan; Sirisomboon, Panmanas (My University, 2022)
A good durian fruit should be supported by sufficient nutrient concentrations. If farmers can quickly determine the nutrient concentration in leaves, they can control fertilisation. Near-infrared (NIR) spectroscopy is a rapid non-destructive test for estimating nutrient concentration. Measuring nutrient concentrations requires chemical analysis and is a time-consuming process. The aim of this paper is a preliminary test for classifying the N, P, and K concentration levels to determine the possibility of creating models in the future to help farmers obtain information on durian tree nutrient requirements quickly. The models reported in this paper were created by PLS-DA, which had higher accuracy than SVM and the SIMCA method. Fresh durian leaf samples were used, and the spectra provided greater accuracy than the dried ground leaf sample spectra. The classification models had an accuracy of 88.89, 81.25, and 86.36% for predicting N, P, and K, respectively.
Keywords: Durian leaf; Near-infrared spectroscopy; Nitrogen; Phosphorus; Potassium